2023
DOI: 10.3390/w15071388
|View full text |Cite
|
Sign up to set email alerts
|

A Regional Water Resource Allocation Model Based on the Human–Water Harmony Theory in the Yellow River Basin

Abstract: Considering the issues of water scarcity, water environment deterioration, and unreasonable allocation of water resources in the urban area of the Yellow River Basin, this paper introduces the human–water harmony theory to the allocation of regional water resources. Based on an analysis of the structural characteristics of the regional water resource system, the harmonious water resource allocation (HWRA) model—which includes three sub-systems (i.e., the water service system, ecological environmental system, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…In addition, the harmonic degree equation (HDE) is also used in water quality assessment studies [4,[28][29][30]. The approach based on harmony theory and the TOPSIS model has been applied in many previous studies, such as allocating water resources [31], determining the level of harmony between water quality and people [4,30,32], and evaluating and ranking water quality [19,25,33,34]. Therefore, applying diverse assessment methods/techniques can overcome the limitations of a single assessment.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the harmonic degree equation (HDE) is also used in water quality assessment studies [4,[28][29][30]. The approach based on harmony theory and the TOPSIS model has been applied in many previous studies, such as allocating water resources [31], determining the level of harmony between water quality and people [4,30,32], and evaluating and ranking water quality [19,25,33,34]. Therefore, applying diverse assessment methods/techniques can overcome the limitations of a single assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Research on human-water harmonious has evolved from qualitative inquiries at the beginning of the 21st century to a more quantitative approach today. Key components of this research now encompass the exploration of interaction mechanisms within human-water systems, the quantitative analysis and simulation of the human-water relationship, and the optimization of schemes promoting such harmony [19][20][21]. These studies have found widespread application across various scales, including national, provincial, urban, and watershed levels.…”
Section: Introductionmentioning
confidence: 99%
“…Groundwater is one of the specific types of mineral wealth, an important resource for life support, development of industry and agriculture [5][6][7]. In terms of increasing deterioration in the quality of surface water, the use of groundwater has several advantages due to their high resistance to climatic factors, protection from pollution, relative stability of quality and quantity over time, absence in most cases of the need for water treatment and seasonal restrictions in their use, etc.…”
Section: Introductionmentioning
confidence: 99%